Dominance of Diffusive Methane Emissions From Lowland Headwater Streams Promotes Oxidation and Isotopic Enrichment - Robison, Andrew L.; Wollheim, Wilfred M.; Perryman, Clarice R.; Cotter, Annie R.; Mackay, Jessica E.; Varner, Ruth K.; Clarizia, Paige; Ernakovich, Jessica G. (Frontiers in Environmental Science, 2022)
Inland waters are the largest natural source of methane (CH4) to the atmosphere, yet the contribution from small streams to this flux is not clearly defined. To fully understand CH4 emissions from streams and rivers, we must consider the relative importance of CH4 emission pathways, the prominence of microbially-mediated production and oxidation of CH4, and the isotopic signature of emitted CH4. Here, we construct a complete CH4 emission budgets for four lowland headwater streams by quantifying diffusive CH4 emissions and comparing them to previously published rates of ebullitive emissions. We also examine the isotopic composition of CH4 along with the sediment microbial community to investigate production and oxidation across the streams. We find that all four streams are supersaturated with respect to CH4 with diffusive emissions accounting for approximately 78 to 100% of total CH4 emissions. Isotopic and microbial data suggest CH4 oxidation is prevalent across the streams, depleting approximately half of the dissolved CH4 pool before emission. We propose a conceptual model of CH4 production, oxidation, and emission from small streams, where the dominance of diffusive emissions is greater compared to other aquatic ecosystems, and the impact of CH4 oxidation is observable in the emitted isotopic values. As a result, we suggest the CH4 emitted from small streams is isotopically heavy compared to lentic ecosystems. Our results further demonstrate streams are important components of the global CH4 cycle yet may be characterized by a unique pattern of cycling and emission that differentiate them from other aquatic ecosystems.